Patients’ and physicians’ preferences for systemic psoriasis treatments: a nationwide comparative discrete choice experiment (PsoCompare) - Schaarschmidt, Marthe-Lisa; Herr, Raphael; Ludwig-Peitsch, Wiebke (Acta dermato-venereologica, 2018)
Systemic antipsoriatic treatment options are increasing rapidly. The aim of this nationwide discrete choice experiment was to compare patients’ (n = 222) and physicians’ (n = 78) preferences for outcome and process attributes of systemic antipsoriatics using Relative Importance Scores (RIS). Both groups considered Psoriasis Area and Severity Index 90 (PASI 90) to be most important (RIS 21.4 and 20.8, respectively). Moreover, patients were highly concerned about mild and severe adverse events (RIS = 18.2 and 14.2), physicians about severe adverse events (RIS = 14.9) and cost (RIS = 13.8). Compared to physicians, patients worried more about mild adverse events and treatment location, but less about cost and frequency of laboratory tests. Physicians’ preferences were influenced by work experience and percentage of biological prescriptions, patients’ preferences by age, disease duration and severity. Older and less severely affected patients recruited via a patient organization focused more on safety, but less on efficacy and time until response than did patients from study centres. In conclusion, these differences in trade-offs should be integrated into a shared decision-making.